DIAGNOSIS KESULITAN BELAJAR FISIKA SISWA KELAS X PADA MASA PANDEMI CORONA DI SMA NEGERI 1 KERITANG. - Selvia Radas Turi; Fakhruddin Fakhruddin; Azhar Azhar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to find out the learning difficulties of students in grade X straight motion materials during the corona pandemic at SMA Negeri 1 Keritang. The population in this study was all students of grade X MIPA at SMA Negeri 1 Keritang. Samples in this study were taken in a simple random sampling so that 29 students were obtained in the study sample. Instruments in this study used diagnostic test (multiple choice four-tier) which is arranged based on syllabus and concept on straight motion material. The data analysis used in this study is descriptive analysis, which gives an overview of students' learning difficulties in straight motion materials during the corona pandemic. The results obtained in this study provide the percentage of average physics learning difficulties of students in grade X straight motion materials during the corona pandemic at SMA Negeri 1 Keritang category understand concept 13.10% (low), category understand the concept of partial 36% (medium), category misconceptions 41% (medium), and categories do not understand the concept of 10.03% (low).Keywords: Pandemic, Learning Difficulties, Diagnostic Tests, Straight Motion